2015
DOI: 10.14710/jitaa.40.3.153-158
|View full text |Cite
|
Sign up to set email alerts
|

COMBINATION OF SOYBEAN MEAL AND Hibiscus tiliaceus LEAF IN THE GOAT DIET: EFFECT ON SOME PARAMETERS OF CARBOHYDRATE METABOLISM

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengkaji efek kombinasi dari daun waru dengan protein bungkil kedelai dalam pakan pada beberapa parameter metabolisme karbohidrat. Materi yang digunakan adalah 16 ekor kambing Peranakan Ettawah berumur 7 bulan dengan bobot badan 16 kg. Perlakuan terdiri dari T0 = Pakan komplit (saponin dan waru 0,90%, PK 8,69%, TDN 62,11%), T1 = T0 + 3% protein bungkil kedelai, T2= T0 + 6% protein bungkil kedelai, dan T3= T0 + 9% protein bungkil kedelai. Penelitian ini dilakukan dengan men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Treatments D1, D2 and D4 were not significantly different but higher than the D3 feed. These results are consistent with the reports of Amaryanti et al (2015) that microbial protein production was not significantly different (P > 0.05) in the use of a combination of soybean meal and Hibiscus tiliaceus leaves in goat feed.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Treatments D1, D2 and D4 were not significantly different but higher than the D3 feed. These results are consistent with the reports of Amaryanti et al (2015) that microbial protein production was not significantly different (P > 0.05) in the use of a combination of soybean meal and Hibiscus tiliaceus leaves in goat feed.…”
Section: Resultssupporting
confidence: 93%
“…As shown in Figure 1, the efficiency of hexose utilization showed is not much different. These results are in line with Amaryanti et al (2015) that found the efficiency of hexose utilization insignificantly different in using the combination of soybean meal and hibiscus leaves in goat feed. 4, microbial protein production showed significant differences between the four treatments.…”
Section: Resultssupporting
confidence: 91%